Adaptation of the Epistemological Belief Questionnaire about Teaching and Learning of Preservice Physics Teacher: Preliminary Research - Kartini Herlina; Doni Andra; I Dewa Putu Nyeneng; B. Anggit Wicaksono; Endang Purwaningsih; Markus Diantoro; Sunaryono Sunaryono (Jurnal Pembelajaran Fisika, 2022)
This study aims to obtain an instrument of teacher beliefs about learning and teaching in hybrid learning in the post-COVID-19 (New Normal) era. In addition to producing a questionnaire instrument, this study looks for the relationship of belief to learning and learning with Confirmatory Factor Analysis (CFA). The research subjects were selected through a random sampling technique (through a lottery) by several teachers/prospective teachers of physics education at schools and in higher education institutions. Structural equation modeling (SEM) analysis was performed using AMOSS v26 using a strong categorical data estimator. The SEM results show the teaching and learning conceptions questionnaire in the marginal fit category (RMSEA) poor fit (NFI, RFI, IFI, TLI, and CGI), in addition, it is shown that the indicators have good internal consistency but lack formation in the latent variance variable. Meanwhile, the results of the SEM Epistemological Beliefs Questionnaire are in the poor fit category, both seen from the RMSEA and NFI, RFI, IFI, TLI, and CGI. Indicators of Fixed ability, learning effort, Authority, and Certainty Knowledge have good internal consistency, while Authority internal consistency is not good. The variance on the Epistemological belief questionnaire extracted from the indicators is greater for the formation of latent variables.Keywords: Adaption, Epistemological belief about teaching-learning questionnaire, Preservice physics teacherDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202213